A people's palace opens: the new Library of Birmingham. Issue 1 (2014) - ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this report is to provide an account of the UK's new public library of Birmingham. Design/methodology/approach – Details the construction, exterior and interior design, contents and location, including special collections, and describes the official opening. Findings – A large public library building which moves away from old conceptions of libraries, accommodating a variety of functions in a striking and accessible building. Originality/value – Provides a description of the new Library of Birmingham, the largest public library in Europe.